2014
DOI: 10.1016/j.tox.2014.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependence in mixture toxicity prediction

Abstract: The value of time-dependent toxicity (TDT) data in predicting mixture toxicity was examined. Single chemical (A and B) and mixture (A + B) toxicity tests using Microtox® were conducted with inhibition of bioluminescence (Vibrio fischeri) being quantified after 15, 30 and 45-min of exposure. Single chemical and mixture tests for 25 sham (A1:A2) and 125 true (A:B) combinations had a minimum of seven duplicated concentrations with a duplicated control treatment for each test. Concentration/response (x/y) data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…A previous study demonstrated that, for binary combinations, averaging the 25, 50 and 75% effect-level TDT values for the individual chemicals over the 15 to 45-min interval could be used to predict MX TDT over the same interval (Dawson et al 2014a). This was done in this study to determine test-to-test consistency of the prediction (Supplementary Table S10).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study demonstrated that, for binary combinations, averaging the 25, 50 and 75% effect-level TDT values for the individual chemicals over the 15 to 45-min interval could be used to predict MX TDT over the same interval (Dawson et al 2014a). This was done in this study to determine test-to-test consistency of the prediction (Supplementary Table S10).…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing the quorum-sensing activity of the marine bacterium Aliivibrio fischeri (Urbanczyk et al 2007), inhibition of bioluminescence was assessed using a calibrated Microtox ® 500 analyzer (Dawson et al 2014a, b). Six experiments were conducted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations